(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Gender bias and color bias has always been a critical social evil in degrading humanity and equality. It has lead to social injustice and curbing of creativity and talent of masses. The creative and hardworking skilled women of color are not acknowledged and appreciated for their work which develops resentment and anger amongst themselves in many countries. Since, diversity is the soil of our mother Earth; we must stand together for an empowered future.